2010
DOI: 10.1007/s10494-010-9279-y
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Preferential Diffusion in Simulations of Premixed Combustion of Hydrogen/Methane Mixtures with Flamelet Generated Manifolds

Abstract: In this paper we study the possibility to account for preferential diffusion effects in lean turbulent premixed flames in numerical predictions with reduced chemistry. We studied the situation when hydrogen is added to methane at levels of 20% and 40% by volume in the fuel, at lean combustion (φ = 0.7) with air. The base case of pure methane was used as a reference. In this case preferential diffusion effects are negligible. First the sensitivity of the mass burning rate to flame stretch was investigated, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…where ρD YZ is the diffusion coefficient for preferential diffusion calculated by the FGM technique. The diffusivity D YZ is related with the non-unity Lewis number, which has been derived by Swart et al [42]. It is worth noting that the species diffusion contribution in Eq.…”
Section: Governing Equations and Chemistry Mechanismmentioning
confidence: 94%
“…where ρD YZ is the diffusion coefficient for preferential diffusion calculated by the FGM technique. The diffusivity D YZ is related with the non-unity Lewis number, which has been derived by Swart et al [42]. It is worth noting that the species diffusion contribution in Eq.…”
Section: Governing Equations and Chemistry Mechanismmentioning
confidence: 94%
“…16 and 17 separately on the predicted autoignition time scales. For this purpose, we define a sensitivity parameter S τ ig that is computed as follows:…”
Section: Comparison Of the Computed Ignition Delay Times Of Differentmentioning
confidence: 99%
“…Successful reduction techniques to accommodate preferential diffusion are mainly based on flamelets [12], such as FGM (Flamelet Generated Manifolds) [13], FPV (Flamelet Progress Variable) [14] and REDIM (ReactionDiffusion Manifolds) [15]. Inclusion of preferential diffusion in FGM has been studied by van Oijen et al [13] and later on by de Swart et al [16] in the context of premixed flames. It has been shown that two controlling variables are needed to account for local variations in equivalence ratio and mass burning rate.…”
mentioning
confidence: 99%
“…[18][19][20][21][22] However, for a compressible flow, the static pressure cannot be assumed constant and may vary by an order of magnitude or more. The effect of p on the chemical kinetics and composition must be considered within the FPV model.…”
Section: Iia Fpv Model Implementation Considerationsmentioning
confidence: 99%